Minat Beli Online Generasi Milenial: Pengaruh Kepercayaan dan Kualitas Layanan - Hana, Kharis Fadlullah (Universitas Islam Negeri Sunan Kudus, 2019)
Buying and selling online is a transaction that is in high demand by the current millennial generation. The ease, efficiency, variety of choices and various promotions offered are the underlying factors for millennials to make online purchases. This can also be seen from the shift in the style of buying the younger generation from traditional markets to online stores that are increasing. Despite the many advantages and advantages offered, there are some consumers who are less satisfied with their purchases online. That is caused by poor service quality because sometimes the response from the seller to the buyer is quite long. Some sellers who give goods that are not in accordance with the offer also cause public confidence to decline. Based on these phenomena, this study aims to determine the effect of service quality and trust in millennial generation consumers' buying decisions and decisions. This research method uses quantitative methods with a Post positivism approach with Structural Equation Model analysis techniques using the WarpPls 6.0 analysis tool. Service quality and trust as exogenous variables, buying interest and online purchasing decisions as endogenous variables. The object of this research is millennial consumers in the cities of Kudus, Jepara and Pati who purchase goods online with a total sample of 375 respondents. The results showed that trust through interest influenced the online buying decision of 0.293. Trust and interest have a total influence of 0.402. Quality of service through interest affects the decision of 0.143. Service quality and interest have a total influence on online buying decisions of 0.363. This means that trust has a greater influence on buying decisions on digital generation compared to service quality.